Pengajaran Bahasa Berdasarkan Teori Aktivitas Budaya Engeström: Integrasi Konteks Budaya dalam Pembelajaran Bahasa - Hasanuddin Chaer; Syamsinas Jafar; Siti Rohana Hariana Intiana; Januari Rizki Pratama R.; Irma Setiawan (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
This article presents a language teaching framework for understanding how human activities can be influenced by social and cultural contexts. This is because effective language teaching does not only understand the structure and vocabulary, but also understands the cultural context in which the language is used. To understand this, this research uses Engeström's 'Cultural Historical Activity Theory' with a qualitative descriptive analytical approach method, with several research steps, First: Identifying Data. Second: Collecting Data. Third: Analyzing Data. Fourth: Synthesis and Interpretation. For this reason, the aim of this research is to discuss the importance of cultural aspects in language teaching and how this approach can improve students' language skills and cultural understanding. The findings of this research indicate that Engeström's culturally-based activity theory can enhance communication skills through language teaching within cultural contexts. Consequently, students can serve as a positive force in fostering cross-cultural communication competence.